O juiz, a propriedade e os conflitos agrários na Paraíba: compreensão decisional como prática social reflexiva - Porto, Giovanni Magalhães (2019)
The proposal contained in the present investigation aims to examine the decisional standards of state magistrates, when judging in the period from 2011 to 2015 twenty-six possessory demands originated from rural conflicts in Paraíba, in consideration of knowing the reason of the understanding of the magistrates of what it is the social function of rural property not to have been able to break through the mechanistic structuralism being an indication of a mere symbolic formalism which violates the requirements of art. 186, of the Federal Constitution. The research sought the critical overcoming of a conservative social praxis, in order to identify a paradigm that surpasses the deficiencies of the structural or agitational models of the theory of law or of the juridical philosophy, brought into by the deficiency of the magistrates failing to identify the habitus which conditions them in the legal field, by embracing a speech of neutrality and universalization. The deconstruction of this pattern limits the exercising of a critical reflexive social practice that would ethically facilitate the acknowledgment of the complex of tensions in the dispute for legal capital and humanistically, the importance of the fight developed by social movements for agrarian reform. For didactic purposes the research is composed of eight chapters and was divided into three parts, which will have as their core, respectively: "The magistrate", in which the process of interpretation and the decisional practice will be examined; "The Earth", in which the right of property and its limitations by the social function will be verified; and finally, "The fight", an opportunity to analyze the legitimacy of the action of anti-systemic movements for the implementation of agrarian reform, proceeding with the investigation of decisions in judicialized agrarian conflicts during the period under a decisional practice objectified on the legal sociology of Pierre de Bourdieu. In like manner, the research will be quali-quantitative in order to provide a better analysis of relations of the actors involved in the Legal Field, through the analysis of cases by the detailed data collection worked on in an internal and crossed way with the intention of pointing, instrumentally, similarities and differences which will allow solving the research objective problem. As for the data collection, the privileged observation and the fundamental collection and examination of data, documents and records were potentiated, which allowed the categories of indicators "language" and "processual" had their content analyzed in the documents collected, with the use of the NVIVO PRO 12 Program from QSR International Pty Ltd.